Measuring the Performance of the Completed Construction Projects through Users Committees: A Case of Khairahani Municipality, Chitwan, Nepal - Koirala, Rajesh (Journal of UTEC Engineering Management, 2023)
The projects in Nepal continuously faces issues of expected performance though at local level performance is strictly time bounded. To measure the performance of the completed construction projects through Users Committees in terms of execution time & cost contribution. The study was solely the project performance of the Municipality implementing through UCs of the 33 sites using Opinion survey, checklist survey. The primary and secondary data and information were collected through different tools as questionnaire survey, Key Informant’s Interview, Checklist and field visits. The Descriptive content analysis produces the measures of selected project performance. Overall performance of project executing by UCs was satisfactory. The projects through UCs have been completed within the budget. There is not time control mechanism in the projects since work schedule was not prepared and followed. Most of projects were completed on time of one year and all projects were completed within estimated cost. Due to less managerial and technical skill of UCs, inadequate supervision by the technicians, unavailability of skill persons at local levels and with no laboratory provision in the projects implementing through UCs, the quality of construction work could not be assured as QAP was not in use. For the transparency, the project information board is displayed at sites in the projects budgeting equal to or greater than 10 lakhs. Public Audits are also conducted in all the projects. The projects after the work completion have been examined and cleared within 30 days after completion. The empirical aspects of project implemented through users committee has been analyzed and pragmatic recommendations have been made for assuring effective performance.